Analysis of the Role of Image Media in the Mathematics Learning Process Amid Technological Development - Sholehah, Alya Jum'atul Sholehah; Kholifah Nur Cahyanti; Nurul Aulia Dini; Nurul Hidayatussolehah (International Journal of Education and Teaching Zone, 2024)
The research carried out aims to analyze the role of image media in mathematics learning amidst the rapid development of technology in order to help students understand and recognize the concept of numbers in mathematics learning. The approach in this research is a quantitative approach, with quasi experimental methods. This research was conducted at SDN 17/XI Simpang Sungai Duren. The population in this study was the first class . Meanwhile, the sample in this study was class 1B, totaling 15 people who were selected using a purposive sampling technique, namely based on the researcher's considerations using opportunity analysis of the material being taught. The data collection technique used by educators uses a test technique in the form of pictorial questions. Meanwhile, data analysis uses classical assessment by comparing the number of answers with the number of questions proportionally. In the research that has been carried out, it was obtained that the percentage of students' scores was very high before and after being given the picture media treatment, namely in terms of recognizing numbers, students' ability to recognize numbers increased from 20% to 90%, then in terms of addition ability, students' ability increased from 10% to 90. % and in the ability to reduce students' ability increased from 30% to 90%. This proves that image media has an important role in mathematics learning, especially for elementary school children.